Modelling of two-phase flow in the human tracheobronchial system - Bayu Wijayanto. (2008)
The existence of solid particles in the air inhaled could have both positive and negative effects towards the overall human respiratory system. Due to the various factors (physiology, flow characteristics, particle charateristics, etc.) involved, numerical method seems to be the best approach. Hence, this project aims to represent the human tracheobronchial system mathematically, to simulate the flow in the 17-th generation of the respiratory airways, which is the entrance to the respiratory zone, and to sutdy effects of solid particles in the alveoli.